Placing land cover preferences by users on the map: Bridging the gaps of landscape preference surveys and spatial pattern analysis in order to inform planning and policy - Carvalho-Ribeiro, Sónia Maria (2012)
Landscapes provide several public goods, which, because they offer social, environmental and economic benefits, have become the focus of policy interest. Land cover patterns, being dynamic landscape components, are essential in delivering public goods. Public goods based on the social demand, such as recreation & landscape appreciation, have been progressively more acknowledged in environmental management as amenity demands steadily increase throughout Europe. As a result, there is a huge body of literature reporting landscape preferences both by the general public and of specific user groups in relation to multiple aspects of European landscapes. However, this empirical work has been revealing enormous challenges to be integrated into landscape planning and policy. This work offers two innovative outputs. One is to progress on gathering user group´s preferred land cover patterns, using in an innovative way, a non spatial model that is meaningful for respondents. The other is to map the preferences by different users into land cover pattern maps in one Alentejo municipality in order to assess the extent to which a certain landscape is likely to meet a specific social demand. Finally, the challenges for integrating the findings of this study into landscape planning and policy are discussed. The other is to relate the preferences expressed by the different users, to the Land Cover Patterns in one Alentejo municipality, to assess the extent to which a certain spatialized landscape has likelihood to meet a specific social demand.